Electrical and thermal effects on electromechanical performance of stretchable thin gold films on PDMS substrates for stretchable electronics - Zhao, Yang (2019)
Stretchable electrodes comprising thin gold films with initial nanocracks on elastic substrates of poly(dimethylsiloxane) are developed in this work, which can be stretched reversibly while maintaining conductivity to an applied uniaxial strain as large as 120%. Reliable electromechanical performance is essential for the application of stretchable electronics as bioelectronic interfaces under various working conditions; therefore, the electrical and thermal effects on the electromechanical performance of the stretchable gold film electrodes are investigated in this work. It is found that the stretchability deteriorates to some extent depending on the electrical and thermal treatments. Microstructures and stress analysis in the cracks are studied, along with crack quantification. It is believed that the decrease of the stretchability is ascribed to the combination of the crack widening by thermal mismatch stress and crack tip smoothening by the electromigration phenomenon. Therefore, the current density and temperature through the electrodes should be controlled within a certain range for wide applications in order to maintain a stable performance of the electrodes. This study also provides some guiding significance for the design of other stretchable electronic devices composed of two materials with large different physical properties.